Stauffer’s Syndrome: A Rare Paraneoplastic Syndrome with Renal Cell Carcinoma - Jain, Mayank; Varghese, Joy; Muruganandham, K M; Venkataraman, Jayanthi (Indian Journal of Medical and Paediatric Oncology, 2018)
An elderly male patient presented with cholestatic jaundice and weight loss. On evaluation, he was found to have left renal mass and hepatomegaly. Diagnosis of Stauffer’s syndrome was confirmed based on his clinical history, biochemical evaluation, and liver biopsy. Resolution of jaundice was noted after removal of the renal mass.
Keywords: Cholestasis; jaundice; paraneoplastic; renal